Adapting business models in buyer-seller relationships: paradoxes in the fast fashion supply chain. Issue 8 (14th December 2020) - Guercini, Simone; Runfola, Andrea
Abstract : Purpose: This paper aims to deal with the issue of business model change in industrial markets. It considers the fast-fashion supply chain by addressing the following research questions: What are the paths of change of the supplier's business model to match the business model of fast fashion customers? How can a supplier's business model be adapted to customer's requirements in these paths of change? Design/methodology/approach: Empirically, the paper presents a multiple case study of 10 semi-finished textile suppliers, carried out through a long-term research programme in the Italian textile industrial district of Prato. Findings: The multiple-case study shows some key drivers of change in the suppliers' business models. Three main paths emerged from the interactions with fast fashion clients. Paradoxes in the supplier's business model changes are identified and discussed. Research limitations/implications: The paper proposes implications for suppliers interacting with fast fashion clients and discusses how the adaptation of business models may be interpreted. This study points out how matching the business model of the customers does not call for alignment of similar features. Originality/value: The paper deals with an understudied topic within the literature: business models change in business to business markets, taking into consideration the perspective of the supplier. It considers buyers-seller relationships in industrial supply chains as being part of a chain of business models and the need for the supplier's business model to adapt and match one of the clients. The paper proposes two potential interpretations of such adaptation.